WORD FORMATION ANALYSIS IN ELON MUSK’S TWEETS AND REPLIES: MORPHOLOGICAL APPROACH - Yosua Timotius Natanael; Feby Septiani; Muhammad Johan (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
Humans have been using creativity to invent new words and expression, through which resulting language to evolve. This process of creating words and expression is called word formation process. Word formation is important to be analysed in order to comprehend the morphological structure and the word origin. By this reason, the aim of this research is to analyse the types of word formation process as well as their part of speech changes in Elon Musk’s tweets. Elon Musk’s tweets and replies in Twitter are full interesting diction of words associated with economy, science and politics. Many words in Elon Musk’s tweets were found unique and could possibly be invented by himself. The researchers used the theory of Yule (2010) in categorizing the types of word formation process, with the addition of two more types brought by O’Grady & Archibald (2015). Furthermore, the researchers categorized the collected data into their part of speech to know how some processes affect the word class. This research is qualitative, and data was collected by using observational method, which then reduced into the tweets and replies from May 15 to June 21, 2022. As the result of this research, it was found that there were 13 acronyms, 12 borrowings, 11 coined words, 7 blend words, 4 clippings, 3 backformations, 34 compound words, 1 onomatopoeia expression, 11 conversions, and 123 derivations, with the total of 218 words. It was also found that word formation process was crucial for the word’s part of speech.